2017
DOI: 10.1177/1748006x17698066
|View full text |Cite
|
Sign up to set email alerts
|

Missing focus on Human Factors – organizational and cognitive ergonomics – in the safety management for the petroleum industry

Abstract: More attention has recently been given to Human Factors in petroleum accident investigations. The Human Factors areas examined in this article are organizational, cognitive and physical ergonomics. A key question to be explored is as follows: To what degree are the petroleum industry and safety authorities in Norway focusing on these Human Factors areas from the design phase? To investigate this, we conducted an innovative exploratory study of the development of four control centres in Norwegian oil and gas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The development and application of new technologies have made systems and organizations more complex (Johnsen et al 2017). Changing analog systems to computer systems in modern control rooms has led to greater complexity and increased human error (Stanton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and application of new technologies have made systems and organizations more complex (Johnsen et al 2017). Changing analog systems to computer systems in modern control rooms has led to greater complexity and increased human error (Stanton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The development and application of new technologies have made systems and organizations more complex ( Johnsen et al. 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature is rich in examples and explanations of why relevant human factors analyses were excluded or inadequately performed, for example, Saetren et al 9 and Johnsen and Liu. 79 We addressed the question 'to what extent is lack of focus on human factors issues linked to known project management challenges?' We found that narrow focus in different project phases and insufficient information coordination contributes to marginalizing the role of human factors in design and development of new technology.…”
Section: Resultsmentioning
confidence: 99%
“…The study (Johnsen et al, 2017) also notes that in aviation, the level of quality of human factor management tools is significantly higher, even in comparison with offshore oil production, so advanced in this field. For the study, the authors analyzed data on the Norwegian PETROMAKS project for 2001-2012.…”
mentioning
confidence: 89%